1994
DOI: 10.1002/esp.3290190507
|View full text |Cite
|
Sign up to set email alerts
|

Holocene valley aggradation and gully erosion in headwater catchments, south‐eastern highlands of Australia

Abstract: Late Quaternary stratigraphy of a 50 km2 catchment on the south-eastern highlands of Australia reveals processes and history of denudation, and helps resolve a long-standing debate about factors controlling episodic valley aggradation and degradation during Holocene times. Valley sedimentation occurred when swampy vegetation fully colonized valley floors and obliterated all channels, promoting aggradation for periods of several thousand years, with most incoming sediment being trapped in swampy meadows. Much o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
95
1
1

Year Published

1996
1996
2004
2004

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 119 publications
(99 citation statements)
references
References 30 publications
2
95
1
1
Order By: Relevance
“…van Dijk, 1959;Walker, 1962;Coventry and Walker, 1977;Prosser et al, 1994) can be correlated with regional events in the manner proposed by Butler (1959) is not critical to interpreting the data reported here. Geomorphic processes active on hillslopes are dependent on the biota of the region and the climate, and it is likely that the lower temperatures of the glacial cycles (by 6-91C, Galloway, 1965;Caine and Jennings, 1968) led to treeless subalpine conditions and periglacial slope processes on the southeastern highlands.…”
Section: Departures From Steady State: (I) Torssupporting
confidence: 50%
See 3 more Smart Citations
“…van Dijk, 1959;Walker, 1962;Coventry and Walker, 1977;Prosser et al, 1994) can be correlated with regional events in the manner proposed by Butler (1959) is not critical to interpreting the data reported here. Geomorphic processes active on hillslopes are dependent on the biota of the region and the climate, and it is likely that the lower temperatures of the glacial cycles (by 6-91C, Galloway, 1965;Caine and Jennings, 1968) led to treeless subalpine conditions and periglacial slope processes on the southeastern highlands.…”
Section: Departures From Steady State: (I) Torssupporting
confidence: 50%
“…Studies of buried and relic geomorphic surfaces have shown how rates and processes have changed in pulses, but have also shown that they can occur without climate changes (e.g. van Dijk, 1959;Walker, 1962;Coventry and Walker, 1977;Prosser et al, 1994). It has also been shown that periglacial processes, thought to be more erosive than processes under milder climates, occurred in the southeastern highlands during the last glacial cycle (Galloway, 1965;Caine and Jennings, 1968;Costin and Polach, 1971;Costin, 1972), and presumably similar processes were active in previous glacial periods.…”
Section: Southeastern Australia Settingmentioning
confidence: 99%
See 2 more Smart Citations
“…Com relação às causas antrópicas tem-se constatado, principalmente, nas primeiras décadas do século XX, em muitas partes do mundo, que a troca de uma agricultura tradicional de baixa intensidade, por práticas de uso do solo mais intensivas (PROSSER et al, 1994), assim como a alteração do curso de um canal original por obras de engenharia e remoção da vegetação das margens dos rios (SCHUMM et al, 2001), vem alterando a dinâmica energética das redes de drenagem naturais (ERSKINE, 1999).…”
Section: Causas Da Incisãounclassified